2016
DOI: 10.1097/mca.0000000000000302
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intracoronary injection of CD133+ bone marrow stem cells on coronary atherosclerotic progression in patients with STEMI

Abstract: Intracoronary injection of CD133(+) bone marrow stem cells has no IVUS-detectable effect on neointimal hyperplasia or atherosclerosis progression in either infarct-related or contralateral arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…IRA analysis revealed similar changes in distal nonstented segment plaque burden between the stem cell and placebo groups (B/L – 41.9 vs. 37.4%, p = 0.56; F/U – 46.7 vs. 40.9%, p = 0.17) [ 44 ]. Findings also were similar for the distal non-culprit segment in patients receiving vs. not receiving stem cells [ 44 ]. Furthermore, in the contralateral coronary artery, there were no differences in changes in MLA, plaque burden, or attenuated plaque between stem cell and placebo patients [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…IRA analysis revealed similar changes in distal nonstented segment plaque burden between the stem cell and placebo groups (B/L – 41.9 vs. 37.4%, p = 0.56; F/U – 46.7 vs. 40.9%, p = 0.17) [ 44 ]. Findings also were similar for the distal non-culprit segment in patients receiving vs. not receiving stem cells [ 44 ]. Furthermore, in the contralateral coronary artery, there were no differences in changes in MLA, plaque burden, or attenuated plaque between stem cell and placebo patients [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the contralateral coronary artery, there were no differences in changes in MLA, plaque burden, or attenuated plaque between stem cell and placebo patients [ 44 ]. The authors concluded that intracoronary injection of CD133 + bone marrow stem cells had no IVUS-detectable effect on neointimal hyperplasia or atherosclerosis progression in either IRA or contralateral arteries [ 44 ]. In aggregate, these studies [ 9 , 44 ] taken together with our present results ( Tables II – IV ) refute early data by Vanderheyden et al [ 15 ] and Mansour et al [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations